Rethinking National Identity Construction Through Independent Films In Indonesia Creative Industry - Idola Perdini Putri; Ellisha Nasruddin; Juliana Abdul Wahab; Iis Kurnia Nurhayati (Universitas Padjadjaran, 2023)
Background: The creative industry in Yogyakarta, since the post-reformation era, specifically the independent film industry, has been producing films that challenge the meaning and interpretation of national identity in its society. Yogyakarta independent films offer different discourses concerning the constructions of national identity. Thus, within this current context of the post-reformation era, the notion of national identity needs proper scrutiny. Purpose: The main purpose of this study is to define and understand the manifestations of Indonesian national identity as depicted in independent films during the post-reformation era within Yogyakarta’s creative city, utilizing Benedict Anderson’s (2006) imagined community concept. Methods: This study conducted a qualitative research methodology using the text analysis of four selected independent films and in-depth interviews with 27 informants located in Yogyakarta. The primary source of the data collected in this study were the textual analyses and the in-depth interviews. Results: The results of this study indicate that within the horizontal comradeship dimension, the notion of multiple interpretations of national identity was highlighted through the issues on the diversity of ethnic identity, modernization, Islamic fundamentalist organization, the promotion of local language, and community attachment to the nation’s symbols. Meanwhile, in the context of the geographical boundaries dimension, the regional attachment within the territory where the communities live implied the important role of the Yogyakarta Monarchy system and as a sovereign power of a Special Region in influencing the diverse interpretations of national identity. Implications: The findings indicated that the past historical meaning of Pancasila, which underscored a requirement for homogeneous identities within the society, contrasted with the evidence found, which demonstrated the evidence of diversity or heterogeneous identity.